Physical and physiological impacts of ocean warming alter phenotypic selection on sperm morphology. (2nd December 2019) - Chirgwin, Evatt; Marshall, Dustin J.; Monro, Keyne
Abstract: Global warming may threaten fertility, which is a key component of individual fitness and vital for population persistence. For males, fertility relies on the ability of sperm to collide and fuse with eggs; consequently, sperm morphology is predicted to be a prime target of selection owing to its effects on male function. In aquatic environments, warming will expose gametes of external fertilizers to the physiological effects of higher temperature and the physical effects of lower viscosity. However, the consequences of either effect for fertility, and for selection acting on sperm traits to maintain fertility, are poorly understood. Here, we test how independent changes in water temperature and viscosity alter male fertility and selection on sperm morphology in an externally fertilizing marine tubeworm. To create five fertilization environments, we manipulate temperature to reflect current‐day conditions (16.5°C), projected near‐term warming (21°C) and projected long‐term warming (25°C), then adjust two more environments at 21°C and 25°C to the viscosity of environments at 16.5°C and 21°C, respectively. We then use a split‐ejaculate design to measure the fertility of focal males, and selection on their sperm, in each environment. Projected changes in temperature and viscosity act independently to reduce male fertility, but act jointly to alter selection on sperm morphology. Specifically, environments resulting from projected warming alter selection on the sperm midpiece in ways that suggest shifts in the energetic challenges of functioning under stressful conditions. Selection also targets sperm head dimensions and tail length, irrespective of environment. We provide the first evidence that projected changes in ocean temperature and viscosity will not only impact the fertility of marine external fertilizers, but expose their gametes to novel selection pressures that may drive them to adapt in response if gamete phenotypes are sufficiently heritable. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.